Letters from Tove - Jansson, Tove (University of Minnesota Press, 2020)
"These letters, penned with characteristic insight and wit, provide an almost seamless commentary on Tove Jansson's life within Helsinki's bohemian circles and on her island home. They summon a particular place and time reflected through a mind finely attuned to her culture, her world, and her own nature, drawing a complex, intimate self-portrait of one of the world's most beloved authors"--